The second founding : how the Civil War and Reconstruction remade the constitution - Foner, Eric, 1943- (W.W. Norton & Company, 2019)
From the Pulitzer Prize-winning scholar comes a timely history of the constitutional changes that built equality into the nation's foundation and how those guarantees have been shaken over time.